POTENSI ANTIBAKTERI EKSTRAK ETANOL DAUN SELUTUI PUKA (Tabernaemontana macrocarpa Jack.) TERHADAP BAKTERI Streptococcus mutans DAN Porphyromonas gingivalis - Sabatini, Sheila Dwi; Handayani, Fitri; Sundu, Reksi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2023)
The Dayak people in West Kutai, East Kalimantan use selutui puka leaves for the treatment of toothache and canker sores. Bacteria that often cause infections in the oral cavity are Streptococcus mutans and Porphyromonas gingivalis. The aim of this study was to determine the activity of the ethanol extract of selutui puka leaves as an antibacterial against Streptococcus mutans and Porphyromonas gingivalis. The research phase involved collecting samples, plant determination, preparing simplicia, preparing extracts and testing antibacterial activity using the paper disc diffusion method with extract concentrations of 15%, 30% and 45%, DMSO negative control 1%, positive control Ciprofloxacin 0.1%. The results showed that the average diameter of the inhibition zone for Streptococcus mutans at an extract concentration of 15% was 17.70 mm (strong), 30% was 19.43 mm (strong), and 45% was 23.60 mm (very strong). ) and against Porphyromonas gingivalis bacteria at an extract concentration of 15% of 17.43 mm (strong), 30% of 23.33 mm (very strong), and 45% of 26.03 mm (very strong).